EDUCATION AND FACTORS AFFECTING CHOICE CAREER OF PUPILS WITH HEARING DISABILITY IN CZECH REPUBLIC - Hrubešová, Ivana; Horváthová, Ivana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The paper focuses on the issues of inclusive education and possible factors that influence the choice of further education and preparation for the professional path of learners with hearing impairment in the Czech Republic. In the research, the survey is based on the quantitative assessment of the factors that may affect the choice of the profession by learners with hearing impairment, in particular, degree of hearing impairment, influence of parents, school, friends, values ​​inculcated in the learning process, and information on education acquisition opportunities. Learners of Form 8 and Form 9 of elementary schools for learners with hearing impairment participated in the survey. Based on the survey, one can speak that elementary schools have low awareness of the equipment possibilities, as well as of small influence of parents and friends on the choice of further education. An important discovery was that learners with hearing impairment do not connect the value of "happy life" with education acquisition, but they consider success at work as an important component of the quality of life.